Partitioning behavior of recombinant lipase in Escherichia coli by ionic liquid-based aqueous two-phase systems. Issue 86 (31st August 2016) - Hadzir, Muhammad Hakimi; Abbasiliasi, Sahar; Ariff, Arbakariya B.; Yusoff, Siti Baidurah; Ng, Hui Suan; Tan, Joo Shun
Abstract : Evaluations of ILATPSs were performed with a variety of ionic liquids and salts as phase components to figure out their competencies in the recovery of lipase from a fermentation broth of E. coli using banana waste as a substrate. Abstract : There has been significant interest in ionic liquid aqueous two-phase systems (ILATPSs) with properties such as rapid phase segregation which can lead to a reduction in time taken for protein recovery. Evaluations of ILATPSs were performed with various types of ionic liquid ((Emim)BF4, (Emim)Br, (Bmim)BF4, and (Bmim)Br) and salts (potassium-, sodium-, and magnesium-based) as phase components to figure out their competencies in the recovery of lipase from a fermentation broth of E. coli using banana waste as a substrate. The results of this study revealed that an ILATPS comprising (Emim)Br/potassium phosphate significantly enhanced lipase recovery upon partitioning lipase. Optimization of the composition of the ILATPS using response surface methodology (RSM) significantly improved the purification factor ( P F ) and partition coefficient ( K e ). The influences of crude loading ( C L ), pH changes, and the presence of NaCl on the recovery performance were also studied. Recovery of E. coli BL21 lipase was accomplished in an (Emim)Br/potassium phosphate ILATPS using 26.5% (w/w) (Emim)Br, 19% (w/w) potassium phosphate at pH 7.6, 3% NaCl and a crude loading of 7% (w/w). Using this ILATPS, lipase was successfully recovered in a single purification step, which gave a yield, P F and K e of 93.75%, 3.394 and 1.352, respectively. A high P F value indicates that (Emim)Br/potassium phosphate is capable of attaining an excellent degree of lipase purity, suggesting that the proposed ILATPS is suitable for implementation in a large scale process for lipase purification.